Vergrößerung des Sehfeldes der Röntgen-Phasenkontrast-Bildgebung für die klinische Anwendung - Schröter, Tobias Jörg (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2017)
X-ray phase contrast imaging is a highly promising technology for the clinical diagnostic. Particularly high demands are placed on the required X-ray gratings, as the core element of this method. Such gratings can be fabricated using LIGA-technology, where the structured area is currently limited to a few centimeters in the diagonal (e.g. 10 cm). In this work possibilities to enlarge the area of X-ray gratings, as they are required for the Talbot-Lau Interferometry, were developed and analyzed.